2017
DOI: 10.9745/ghsp-d-16-00395
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading Supply Chain Management Systems to Improve Availability of Medicines in Tanzania: Evaluation of Performance and Cost Effects

Abstract: Investments in a national logistics management unit and electronic logistics management information system resulted in better data use and improvements in some, but not all, management practices. After 1 year, key improvements included reduced stock-out rates, stock-out duration, and expiry rates. Although the upgraded systems were not inexpensive, they contributed to greater system efficiency and generated modest savings that defrayed much of the investment and maintenance costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 1 publication
(1 reference statement)
1
20
0
1
Order By: Relevance
“… 44 A study conducted in a different setting in Tanzania showed that staff training on the web-based electronic logistics management information system (eLMIS) intervention accounted for >50% of the investment costs, however, there were enormous cost savings after upgrading the eLMIS. 45 …”
Section: Discussionmentioning
confidence: 99%
“… 44 A study conducted in a different setting in Tanzania showed that staff training on the web-based electronic logistics management information system (eLMIS) intervention accounted for >50% of the investment costs, however, there were enormous cost savings after upgrading the eLMIS. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Investment in technology over time allows the system to keep pace with innovative ways to collect, manage, and analyze data. 7,12 Early cost-bene t analysis of some Tanzania upgrades to the HIS have shown a nancial bene t, though additional bene ts may not be seen for several years [33].…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, the MOHCDGEC began working with the USAID | DELIVER Project and other partners to improve national health information logistics and strengthen human capacity and systems design. This work led to implementation of the Integrated Logistic System Gateway, a mobile reporting system designed to increase the visibility of logistics data and improve product availability, and subsequently the electronic Logistics Management Information System (eLMIS), which increases supply chain visibility at all system levels [31][32][33]. Other routine and non-routine health information were collected through household surveys (such as the Demographic and Health Surveys), health facility and administrative databases, census and vital events registration data, the Integrated Disease Surveillance and Response framework for communicable disease surveillance, and mobile technology for data collection on immunizations and neglected tropical diseases [35][36][37][38].…”
Section: Building Tanzania's Health Information Systemmentioning
confidence: 99%
“…Tanzania's public health supply chain system serves the MOHCDGEC-operated facilities, including 20 regional vaccine stores, 137 district stores, and 6.821 service delivery points (hospitals, health centres, and dispensaries). The value of medicines and other commodities moving through the public health supply chain each year is roughly 300 billion Tanzanian shillings (TSh) (14).…”
Section: Study Settingmentioning
confidence: 99%
“…The MOHCDGEC has overall responsibility for ensuring the system remains functional. System logistics are run by the MSD, a semi-autonomous organisation in MOHCDGEC (14,15). At the district level, the forecast and ordering of commodities is done by district pharmacists, whose supervision lies under the President's O ce Regional Administration and Local Government (PORALG), as part of Tanzania's decentralized system (16).…”
Section: Study Settingmentioning
confidence: 99%